(untitled) (Journal of history, 2022)
The article characterizes the sources of the history of education in the 1920-1930s. It describes the funds and documents of the Central State Archive of the Republic of Kazakhstan, the archive of the President of the Republic of Kazakhstan, the state archives of Almaty, Kyzylorda, Turkestan, Orenburg regions and the state archives of the Russian Federation. Are characterized funds 4, 5, 127, 173, 194, 377 of the Kyzylorda Regional State Archive The value of the 77th fund of the state archive of the city of Almaty is estimated. Information about the development of education in the republic is given in the collection “Materials for the report of the Central Executive Committee of the Kazakh ASSR at the 3rd session of the All-Russian Central Executive Committee of the 13th convocation.” The content of the collection of documents and materials “People’s education of the Kazakh SSR” is revealed. The role of the collection “Cultural Construction in Kazakhstan” in the study of the history of the formation of the Soviet education system is assessed, in which protocols, resolutions of the Turkestan Central Executive Committee and the Council of People’s Commissars, resolutions of district committees and city committees of the party, orders and instructions of departments of public education, etc. were introduced. organization and management of education in the 1920s. prepared on the basis of documents of the Central State Archive of the Republic of Uzbekistan. Are considered Periodicals published in 1918-1930 and articles on their pages.